Substance abuse in high school students in association with socio-demographic variables in northwest of iran. - A Mohammadpoorasl; S Nedjat; A Fakhari; K Yazdani; A Rahimi Foroushani; A Fotouhi (Tehran University of Medical Sciences, 2012)
Substance abuse in adolescents and its often tragic consequences, including addiction, is one of the preventable major public health problems. The aims of this paper were to estimate the prevalence of substance abuse and to evaluate its some associated factors in adolescents of Tabriz City (northwest of Iran).A self-administered questionnaire was completed in 4903 randomly selected students with mean age of 15.7 years old. The aim of the questionnaire was obtaining information on substance abuse, socio-economical information, cigarette smoking behavior, general risk taking behavior, self-esteem, attitude towards smoking and self-injury as well as demographical characteristics.Prevalence of substance abuse was 1.4% (95% CI: 1.1-1.7) which was different statistically significant between boys (2.4%) and girls (0.6%) (P